Evaluasi pengelolaan dana Bantuan Operasional Sekolah (BOS) di SD Negeri 76 Manado - Turambi, Krisno; Budiarso, Novi Swandari; Kalalo, Meily Y. B. (Riset Akuntansi dan Portofolio Investasi, 2024)
The School Operational Assistance (BOS) program is an initiative of the Indonesian government to support school operational costs and improve the quality of education. However, in its implementation, misuse of funds often occurs which affects accountability. Based on this problem, this study aims to evaluate the mechanism of management, use and accountability of BOS funds with the research object SD Negeri 76 Manado based on Permendikbudristek Number 63 of 2023. The research method used was descriptive qualitative, with data collected through interview sessions and documentation. The results showed that the BOS fund management mechanism at SD Negeri 76 Manado had followed the applicable regulations, but there were several obstacles such as changes in the price of goods that affected budget planning. In the use of funds, allocations were made in stages for two semesters and adjusted based on an evaluation of actual needs. Accountability is carried out through a report on the realization of the use of funds prepared every semester. The study concludes that despite efforts to manage funds transparency and accountability, improvements are still needed in supervision and planning adjustments to overcome external constraints and ensure more efficient use of funds. In relation to unforeseen needs, including the cost of emergency repairs, health and security costs, and the procurement of additional teaching materials, there was no effective mechanism for managing the use of BOS funds.